Síntese de novas amidinas triazólicas com potenciais antagonistas do NMDA subtipo NR2B no Sistema Nervoso Central - Marins, Luana Monteiro Spíndola (2006)
Three novel amidines containing the 1,2,3- and 1,2,4-triazole moiety with potential NMDA/ NR2B antagonist activities in the central nervous system were synthesized: N-(5- trifluormethyl-2H-[1,2,4]-triazole-3-yl)-benzamidine (II), N-benzyl-2-phenyl-2H-[1,2,3]-4- carboxamidine (III) and 2-phenyl-N-(5-trifluormethyl-2H-[1,2,4]-triazole-3-yl)-2H-[1,2,3]- triazole-4-carboxamidine (IV). While amidine II has been prepared from reaction of benzonitrile and 3-amino-5- trifluormethyl-1H-1,2,4-triazole (2) promoted by CuCl at 80oC, the compounds III and IV were prepared from reactions of the 2-phenyl-2H-[1,2,3]-triazole-4-carbonitrile (5) with the appropriate amines, namely benzylamine or amine 2, respectively. In the syntheses II, III and IV carried out by sonication, faster reactions were obtained without loose of chemical yield. Biological activity of the prepared compounds was measured in purified cultures of retinal neurons and photoreceptors. Initial experiments showed that amidines II and III have neuroprotective effects without themselves inducing neurotoxicity. Pretreatment of cultures with amidines II and III inhibited the cell death induced by glutamate: neurotoxicity was reduced by 48 or 60% when amidine II or amidine III, respectively, was present during glutamate exposure.